Analysis of Corrosion Resistant Steel Coating Using Hot Dip Galvanization Method and Polarization / Tafel Test - Faris Abdullah; Prantasi Harmi Tjahjanti (Procedia of Engineering and Life Science, 2021)
Hot Dip Galvanization (HDG) is a method of plating steel by immersing liquid zinc. However, in this study, HDG was tried by dipping steel in a solution of cast aluminum waste, after being coated with galvanizing and graphene. Furthermore, the corrosion test is carried out using the tafel or polarization test aid. The aim of this research is to protect the corrosion attack on steel by means of HDG in a solution of cast aluminum waste, after being coated with galvanizing and graphene. The solution in the tafel test used NaCl solution. The results obtained were the least corrosion attacks on steel with a galvanic coating and graphene. Meanwhile, HDG with cast aluminum waste is not significant to protect corrosion on steel.